Analisis Efektivitas Artificial Intelligence dalam Keputusan Pembelian Generasi Z: Studi Kasus pada Produk Gaenier di Platform Shopee - Saputra, Rico Dharma; Wedagama, Dewa Ayu Trisna Adhiswari (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effectiveness of artificial intelligence (AI) in influencing Generation Z consumer purchasing decisions with trust (trust) as a mediating variable. This study focuses on Garnier cosmetic products marketed through the Shopee e-commerce platform. The research approach used is quantitative with a survey method of 160 Generation Z respondents who are active Shopee users and have experience using AI-based features, such as skin analysis and product recommendations. Data were collected through a questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of SmartPLS 4 software. The results show that artificial intelligence has a positive and significant effect on consumer trust. In addition, trust has a positive and significant effect on purchasing decisions. Artificial intelligence also has a direct effect on purchasing decisions, while trust is proven to partially mediate the relationship between artificial intelligence and purchasing decisions. This study confirms that the use of AI technology has an important role in building consumer trust and supporting Generation Z purchasing decision making on e-commerce platforms.